Misdiagnosed ectopic pregnancy mimicking adnexal malignancy: a report of two cases. (31st January 2013) - Savelli, L.; Fabbri, F.; Moruzzi, C.; Testa, A. C.
ABSTRACT: We present two cases of nulliparous women with no history of amenorrhea who were referred to our unit following finding of a hypervascularized solid adnexal mass. In both cases a malignant tumor of tubal origin was suspected at transvaginal sonography. However, following laparoscopy, histological examination revealed that the masses were the result of an undetected tubal ectopic pregnancy that had failed spontaneously, with massive vasodilatation of pelvic blood vessels surrounding the trophoblastic tissue. We recommend consideration of the potential diagnosis of a previously undetected, failed tubal ectopic pregnancy in fertile women presenting with an adnexal mass, even when there is no history of amenorrhea or a positive pregnancy test.